Relationship of Mother Characteristics With Compliance of Visiting Posyandu to Between Ages 1-5 Years Old in Sugihwaras Puskesmas, Teluk Gelam District, Ogan Komering Ilir Regency in 2022 - Sri Munjayatun; Helni Anggraini; Eka Afrika (Institute of Computer Science (IOCS), 2022)
Posyandu is a form of Community Resource Health Effort (UKBM) which is managed from, by, for and with the Community, to empower and provide facilities for them in obtauining basic health services. The impact on toddlers when mothers are not active in weighing activities in the posyandu eg does not get health education, does not get vitamin A, mothers do not know the growth and development of underweight children, mothers do not get information and counseling about supplementary food (PMT). This condition causes nutritional problems in toddlers which have a fatal impact that can cause death. The current phenomenon is that not all mothers are willing to visit the Posyandu every Month. The Purpose: of this study was to determine the relationship between mothers occupational status and knowledge about Posyandu with the compliance of Posyandu visits. This Study use an analytical survey with Cross-Sectional design. Sampling was done by accidental Sampling with multiple logistic regression data analysis. Wald test showed that there was a relationship between occupational status and compliance to visit Posyandu Toddler and was statistically significant (p=0.611). There was a re relationship between mothers knowledge about Posyandu and compliance to visit Posyandu Toddlers and statistically significant (p=0.021). There was a relationship between mothers Age about Posyandu and compliance to visit Posyandu Toddlers and statistically significant(p=0.029). There was a relationship between mothers characteristic with Compliance to visit Posyandu Toddler at Sug Ihwaras Public health care, Teluk Gelam District, Ogan Komering Ilir Regency in 2022.